Resveratrol Enhances the Anti-Cancer Effects of Cis-Platinum on Human Cervical Cancer Cell Lines by Activating the SIRT3 Relative Anti-Oxidative Pathway - Jiang, Bin; Tian, Qi; Shu, Chuqiang; Zhao, Jing; Xue, Min; Zhu, Shujuan (Frontiers in Pharmacology, 2022)
Background: Cervical cancer exerts considerable mortality in the world. The combinations of chemotherapy with cis-platinum were the first-line treatment in late-stage cervical cancer but may cause severe adverse effects. Resveratrol (RES, 3,5,4′-trihydroxy-trans-stilbene) is a phytoalexin, and it showed anti-cancer effects but with low toxicity and side effects. Herein, we examined the anti-cancer effects of cis-platinum combined with RES in human cervical cancer cell lines. Methods: The antiproliferative effect was examined by cell counting and short-term MTT assay. Cell apoptosis was detected. The cell cycle distribution was determined by flow cytometry. Intracellular reactive oxygen species and mitochondrial transmembrane potential change were observed and calculated by confocal microscopy. The Si-RNA interference of SIRT3 in cancer cells was performed. Protein expression was checked by Western blotting. Results: RES inhibited the growth of SiHa cell lines, and it significantly enhanced the cis-platinum-induced cell apoptosis and cell cycle arresting in 48 h. The activation of the SIRT3 relative anti-oxidative pathway was proved to be the reason for the enhanced anti-cancer effects of cis-platinum and RES combination. Si-RNA interference of SIRT3 compromised the anti-cancer effect of cis-platinum and RES combination. Furthermore, the silencing of SIRT3 RNA inhibited the expression of the anti-oxidant enzyme (MnSOD, GPx, SOD-1, and CAT) and decreased the generation of H2O2 in the cis-platinum and RES combination group. Conclusion: RES enhances the anti-cancer effects of cis-platinum on SiHa cells by activating the SIRT3 relative anti-oxidative pathway. RES may act as a potential synergistic agent and be useful in the treatment of cervical cancer.